Analysis of Risk Factors for Mean Arterial Pressure and Body Mass Index on the Incidence of Preeclampsia - Nur Purnama Sari; Ramesia Ratnawati; Satra Yunola; Helni Anggraini; Elvina Indah Syafriani (Journal La Medihealtico, 2026)
Preeclampsia is a major cause of maternal and perinatal morbidity and mortality worldwide, including in Indonesia. Early screening during pregnancy allows for early identification and optimal patient monitoring. This study aimed to analyze the relationship between Mean Arterial Pressure (MAP) and Body Mass Index (BMI) with the incidence of Preeclampsia, and to determine the most dominant factor in the working area of Pakjo Community Health Center (Puskesmas) Palembang. This study used a Case-Control design. The sample consisted of 62 pregnant women, divided into 31 Preeclampsia cases and 31 Non-Preeclampsia controls, derived from medical record data for the 2023–2024 period. Data analysis utilized the Chi-Square test for bivariate analysis and Binary Logistic Regression for multivariate analysis. Bivariate Analysis: A statistically significant relationship was found between Positive MAP (p < 0.001, OR = 6.597) and Overweight/Obese BMI (p < 0.001, OR = 8.381) with the incidence of Preeclampsia. Multivariate Analysis: After controlling for MAP, only High BMI proved to be a significant independent predictor (p = 0.030). Pregnant women with High BMI had a 4 times greater chance of experiencing Preeclampsia (OR = 4.848; 95% CI: 1.165–20.182). The MAP variable became non-significant in the multivariate model (p = 0.234). High BMI (Obesity/Overweight) is the most dominant risk factor and a strong independent predictor for the incidence of Preeclampsia. It is recommended that Pakjo Community Health Center prioritize intervention programs focused on weight management and nutrition counseling starting from the pre-pregnancy and early pregnancy periods as a primary effort to prevent Preeclampsia.